2014
DOI: 10.1111/grs.12075
|View full text |Cite
|
Sign up to set email alerts
|

Conditions that favor clover establishment in permanent grass swards

Abstract: Over seeding clover into permanent grasslands has many benefits, but successful establishment can be difficult as it depends on multiple interacting variables. This paper reports on a 2‐year factorial experiment conducted to evaluate how the interaction of several variables: (i) height of residual grass stubble at sowing, (ii) defoliation frequency, and (iii) fertilization with P and K affected clover seedling emergence and subsequent biomass in a permanent grass sward. In 2010, a red clover (Trifolium pratens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…A recent study that evaluated the effect of high-density grazing in grass-legume mixtures found that intense grazing reduced persistence of several planted legumes, but that white clover was negatively impacted the least [32]. Erect-growing legumes such as red clover should be able to compete well with grasses for light [33, 34, 35], and we found that red clover did respond positively to mob stocking (Fig 3). Grazing in late fall, and favorable weather conditions also likely helped to promote clover abundance.…”
Section: Discussionmentioning
confidence: 55%
“…A recent study that evaluated the effect of high-density grazing in grass-legume mixtures found that intense grazing reduced persistence of several planted legumes, but that white clover was negatively impacted the least [32]. Erect-growing legumes such as red clover should be able to compete well with grasses for light [33, 34, 35], and we found that red clover did respond positively to mob stocking (Fig 3). Grazing in late fall, and favorable weather conditions also likely helped to promote clover abundance.…”
Section: Discussionmentioning
confidence: 55%
“…In the 125 DD interval, frequent defoliation allowed for greater luminosity at the base of the canopy, and likely also reduced the organic reserves for the cold season forage species, in response to the low leaf area index, and promoting the interaction between warm season species in the canopy. Red clover does not support intense grazing and becomes dominated by other components of the canopy when subjected to frequent cutting (TRACY et al, 2014), which was observed in the 125 DD interval. A high and positive correlation for ryegrass existed according to the percentage of species interaction with red clover and canopy height in all the cut interval, except for 125 DD (250, 375, and 500 DD; r = 0.83; P = 0.019).…”
Section: Discussionmentioning
confidence: 95%
“…Successful establishment of clover seedlings into permanent grassland depends on a number of factors and their interactions. For example, [30] points out a large influence of cutting frequency, stubble height and its interaction with P and K nutrition. Indeed, P nutrition in trials with failed WC establishment [19] was lower than in our current study (current trial: P CAL extract 20.3 mg P 2 O 5 100 g −1 , failed WC trial: 11mg P 2 O 5 100 g −1 ).…”
Section: Discussionmentioning
confidence: 99%